Greenland, inner end of Kejser Franz Joseph Fjord - Boyd, Louise Arner, 1887-1972 (1931)
July 29, 1931. Kaiser Franz Josef Fjord. Inner end. On left, Riddarborgen. S.W. point at entrance to Kaiser Franz Josef Fjord. In background, extreme inner end of Kaiser Franz Josef Fjord., showing Nordenskjold Glacier. On right, mts. on Fraenkels Halvo forming north side of Kaiser Franz Josef Fjord. Photo taken looking W.N.W. from S.S. Veslekari.